Future perspective of stem cell-derived exosomes: Cell-free therapeutic strategies for retinal degeneration - Liu, Zibin; Zeng, Fang; Zhang, Yao; Liu, Yongqing; Li, Zhuo; Liu, Xiao (Frontiers in Bioengineering and Biotechnology, 2022)
With continued expansion of the aged population, the number of patients with retinal degeneration, which is a leading cause of vision loss worldwide, is growing. Stem cell therapies offer hope for regeneration and repair of damaged retinal tissue. Recent reports have highlighted stem cell-derived paracrine mediators, such as exosomes, which appear to exert a therapeutic benefit similar to their cell of origin and do not carry the risk of cell transplantation. One speculated role is that exosomes likely mediate intercellular communication and material exchange. This review depicts the molecular mechanisms underlying exosome-based therapy, especially in retina degeneration diseases. In the future, the use of stem cell-derived exosomes could be considered a novel and cell-free therapeutic strategy in regenerative medicine.